Nilai-Nilai Karakter Dalam Proses Pembelajaran Puisi DiKelas VII SMP Negeri 2 Tawangmangu - Jayanti, Tyas Dwi; , Drs.Adyana Sunanda, M.Pd (2016)
The aim of this study to describes: (1) how to apply character's values in poetry learning Bahwa Kita Ditantang Seratus Dewa by W.S Rendra for clas VII, (2) character's values through a poetry learning process Bahwa Kita Ditantang Seratus Dewa by W.S Rendra for class VII; and (3) the result of poetry learning Bahwa Kita Ditantang Seratus Dewa by W.S Rendra for clas VII. This study uses descriptive qualitative research. The main of data resources in qualitative research are poetry, teaching and learning, word, phrase, figure of speech which contains the character values. The data was collected by using observation technique, interview, field note, document usage. The result of the research indicates such as: (1) applying the method of character's value in poetry learning process Bahwa Kita Ditantang Seratus Dewa by W.S Rendra clas VII, such as; a) arranging the syllabus, b) arranging of RPP, c) learning method, d) analysing the poetry Bahwa Kita Ditantang Seratus Dewa by W.S Rendra class VII SMP Negeri 2 Tawangmangu, e) learning process; (2) character's values through poetry learning Bahwa Kita Ditantang Seratus Dewa by W.S Rendra describe values that include in poetry learning process. Each process of learning include the character's value. Based on the datas above there are eighteen character's value that do not include in Kemendikbud and do include in Kemendikbud, that explain such as; dicipline's value, religius, diligent, caring, good manners, logical, creative, independent, cooperation, mutual respect, environtment caring, confident, critical, responsible, patriotism, hard work, appreciate the achievements, social caring, understand the advantages and disadvantages, honest's value; (3) The learning result of poetry covers affective and cognitive. Keyword: poetry analysis, character's value, learning process